Increasing Learning Results with Interactive Digital Materials PjBL Assisted by Heyzine Flipbook Maker - Muhaimin Muhaimin; Leny Leny; Almubarak Almubarak (Journal of Mathematics Science and Computer Education, 2024)
The internet has not been optimally utilized to support student learning, especially chemistry. Therefore, a research study was conducted to develop interactive digital teaching materials as an interactive e-module supported by the Heyzine application on colloids. This study aimed to develop teaching materials that possess (a) validity, (b) practicality, and (c) effectiveness. The research employed a Research and Development (R&D) approach with a 4D development model (Define, Design, Develop, & Disseminate). The developed e-module was tested on grade XI MIPA 2 students at SMA Negeri 10 Banjarmasin during the 2022/2023 academic year. The testing was conducted individually, in small groups, and a limited manner. Data was collected using questionnaires for validation, readability, response, and test assessment. Descriptive analysis was used to analyze the data. The results showed that the developed e-module met the validity, practicality, and effectiveness criteria. The validity test results indicated a high level of validity, with an average score of 95.64%. The e-module was also found to be practical based on the readability test, student and teacher response questionnaires, and the observation of teacher's abilities and implementation of learning. The practicality test scores indicated good to excellent quality. Furthermore, the limited testing demonstrated the effectiveness of the e-module in achieving learning objectives, as indicated by a high average n-gain score of 0.74. Overall, the developed e-module was able to enhance students' knowledge and learning outcomes in the field of colloids.